Salmonella enterica serovar Typhimurium interaction with dendritic cells: impact of the sifA gene. - Petrovska, L; Aspinall, R; Barber, L; Clare, S; Simmons, C; Stratford, R; Khan, SA; Lemoine, N; Frankel, G; Holden, D; Dougan, G (2004)
Salmonella enterica serovar Typhimurium (S. Typhimurium) and several mutant derivatives were able to enter efficiently murine bone marrow-derived dendritic cells using mechanisms predominantly independent of the Salmonella pathogenicity island 1 type III secretion system. The levels of intracellular bacteria did not increase significantly over many hours after invasion. Using fluid endocytic tracers and other markers, S. Typhimurium-containing vacuoles (SCVs) were physically distinguishable from early endocytic compartments. Fifty to eighty per cent of SCVs harbouring wild-type S. Typhimurium or aroA, invH and ssaV mutant derivatives were associated with late endosome markers. In contrast, S. Typhimurium sifA was shown to escape the SCVs into the cytosol of infected dendritic cells. S. Typhimurium aroC sifA was more efficient than S. Typhimurium aroC in delivering a eukaryotic promoter-driven green fluorescent protein reporter gene for expression in dendritic cells. In contrast, S. Typhimurium aroC sifA did not detectably increase the efficiency of MHC class I presentation of the model antigen ovalbumin to T cells compared to a similar aroC derivative. Mice infected with the S. Typhimurium aroC sifA expressing ovalbumin did not develop detectably enhanced levels of cytotoxic T cell or interferon-gamma production compared to S. Typhimurium aroC derivatives.